2010
DOI: 10.1017/s0022215110002100
|View full text |Cite
|
Sign up to set email alerts
|

Rigid endoscopic evaluation of conventional curettage adenoidectomy

Abstract: Conventional curettage adenoidectomy misses a substantial amount of adenoid tissue. Rigid endoscopy-assisted adenoidectomy improves this result by enabling localisation of any residual adenoid tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 11 publications
0
27
0
2
Order By: Relevance
“…Nonvisualized curette technique with digital palpation to confirm completeness of adenoid removal reported residual adenoid tissue in 80% of cases 12. Endoscopic evaluation immediately after curettage has shown residual adenoid tissue in >60% of patients 13. Other groups have advocated the use of transnasal endoscopy and microdebrider to remove residual adenoid tissue remaining after curette adenoidectomy 14…”
Section: Discussionmentioning
confidence: 99%
“…Nonvisualized curette technique with digital palpation to confirm completeness of adenoid removal reported residual adenoid tissue in 80% of cases 12. Endoscopic evaluation immediately after curettage has shown residual adenoid tissue in >60% of patients 13. Other groups have advocated the use of transnasal endoscopy and microdebrider to remove residual adenoid tissue remaining after curette adenoidectomy 14…”
Section: Discussionmentioning
confidence: 99%
“…With the evolution of endoscopic sinus surgery [2, 4, 5, 16, 17], the introduction of endoscopic vision during curettage adenoidectomy seems rational and optimal compared to use of the mirror for indirect vision. Several manipulations have been adopted to improve the adenoidectomy technique by introducing different surgical instruments from different routes under endoscopic vision, for example, transoral adenoidectomy guided by transoral or transnasal endoscope and transnasal adenoidectomy guided by transnasal or transoral endoscope [1].…”
Section: Discussionmentioning
confidence: 99%
“…Saxby and Chappel [14] found some residual adenoidal tissues evident on nasopharyngoscopy in 68%, of which 24% had significant obstruction. Also, Regmi et al [15] reported that conventional curettage adenoidectomy usually misses a substantial amount of adenoid tissue in more than 60%. By the end of a 2-year follow-up, recurrent obstructive adenoid was detected in 6.6% of cases that were not subjected to nasopharyngeal endoscopic exploration, while it was detected in 1.18% of cases that were explored with cauterization of any residual adenoidal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Ezzat [17] studied 312 adenoidectomy patients; with endoscopic examination of 122 patients, he found residual obstructive adenoidal tissues that were missed after conventional adenoidectomy in 14.5%, however, adenoidectomies were not done by a single surgeon with different experience and surgical talent between otolaryngologists, telephone questionnaire was used in the follow-up of patients and it showed recurrence in 5.6% in the non-endoscopically examined group while it was 0.85% in the endoscopically examined group. As recurrence of nasal obstructive symptoms after conventional adenoidectomy is not rare, many authors recommended endoscopic assisted technique for more complete removal and consequently to decrease the recurrence rate [15,[17][18][19].…”
Section: Discussionmentioning
confidence: 99%